Factors influencing herpetofauna abundance and diversity in a tropical agricultural landscape mosaic. (16th June 2020) - Ghosh, Deyatima; Basu, Parthiba
Abstract: Agricultural intensification and the associated factors, including land transformation, are among the major global threats affecting biodiversity especially herpetofauna. However, little information is available about how different factors shape herpetofauna species assemblages in agricultural landscape at different spatial scales from patch (125 – 250m) to the landscape (500 – 1000m). We assessed the diversity of amphibians and reptiles in areas under low and high degrees of agricultural intensification and explored different factors regulating diversity at different spatial scales using four sampling methods. Diversity and abundance of amphibians varied significantly between the two zones, but not for reptiles. Agricultural intensification index (AII), calculated based on agrochemical use and area under agriculture at 250m scale, seemed to affect amphibians both at patch as well as at 500m and 1000m landscape scales. The AII influenced reptilian diversity only at patch and 500m scales. Vicinity of natural forest had a stronger influence on reptilian abundance. Seminatural vegetation impacted herpetofauna diversities at larger spatial scales. The extent of water bodies influenced the reptilian abundance at 250m patch scale and amphibian abundance both at 250m and 1000m scale. Fallow lands affected only reptilian diversity at all spatial scales. Plantation affected amphibian at all scales but reptiles only at the landscape scale. Habitat heterogeneity regulated only amphibian diversity. These results highlight the fact that different patch and landscape‐scale factors regulate the diversity of reptiles and amphibians differentially. Such scale‐specific information will crucially inform future conservation action for the herpetofauna in the agricultural landscape.